2014
DOI: 10.1016/j.ijid.2014.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and laboratory profiles of refractory Mycoplasma pneumoniae pneumonia in children

Abstract: This study indicates that a direct microbe effect and the subsequent induced excessive host immune response contribute in part to the progression of RMPP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
92
1
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(110 citation statements)
references
References 34 publications
13
92
1
4
Order By: Relevance
“…However, longer duration of fever, longer length of stay, and higher incidence of extra-pulmonary complications were found in the RMPP group than those in the GMPP group, which indicated that to some extent children with RMPP had a more severe illness. With respect to radiological findings, pleural effusion and large lesions were more frequently found in the RMPP group than those in the GMPP group, which were similar to previous reports816.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…However, longer duration of fever, longer length of stay, and higher incidence of extra-pulmonary complications were found in the RMPP group than those in the GMPP group, which indicated that to some extent children with RMPP had a more severe illness. With respect to radiological findings, pleural effusion and large lesions were more frequently found in the RMPP group than those in the GMPP group, which were similar to previous reports816.…”
Section: Discussionsupporting
confidence: 91%
“…In our other study, we found that the incidence of RMPP in school-aged children was more common than younger children (data not published). Some studies816 also found that children with RMPP were significant older (the mean age was 66.6~73.2 months) than children with GMPP. So age should be one of confounders of some clinical presentation and biological markers because children were in the process of growing.…”
Section: Discussionmentioning
confidence: 95%
“…La mayoría de las infecciones por M. pneumoniae generalmente son leves y auto limitadas; sin embargo, en la actualidad se reconoce que puede ocasionar cuadros graves y refractarios como neumonía fulminante, neumonía necrotizante y desarrollo del síndrome de dificultad respiratoria del adulto (SDRA). 51 También se ha asociado a otras infecciones del tracto respiratorio superior como: faringitis, bronquitis, laringotraqueítis, rinosinusitis, otitis media, miringitis y bronquiolitis. 52 Además, causa una gran variedad de infecciones extrapulmonares que afectan prácticamente a cualquier órgano.…”
Section: Manifestaciones Clínicasunclassified
“…61 También se ha encontrado que en cuadros más graves y refractarios se observan más las consolidaciones segmentaria-lobar (50-62%), así como incremento en el derrame pleural hasta el 22%. 51 …”
Section: Estudios De Imagenunclassified
See 1 more Smart Citation